Direct limits on the B-s(0) oscillation frequency - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Amer Physical Soc, 2006)
We report results of a study of the B-s(0) oscillation frequency using a large sample of B-s(0) semileptonic decays corresponding to approximately 1 fb(-1) of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider in 2002-2006. The amplitude method gives a lower limit on the B-s(0) oscillation frequency at 14.8 ps(-1) at the 95% C.L. At Delta m(s)=19 ps(-1), the amplitude deviates from the hypothesis A=0 (1) by 2.5 (1.6) standard deviations, corresponding to a two-sided C.L. of 1% (10%). A likelihood scan over the oscillation frequency, Delta m(s), gives a most probable value of 19 ps(-1) and a range of 17 <Delta m(s)< 21 ps(-1) at the 90% C.L., assuming Gaussian uncertainties. This is the first direct two-sided bound measured by a single experiment. If Delta m(s) lies above 22 ps(-1), then the probability that it would produce a likelihood minimum similar to the one observed in the interval 16-22 ps(-1) is (5.0 +/- 0.3)%.